Construction Claim Recognition Challenges in State-Owned Enterprises : A Case Study in Indonesian SOEs - Borkat, Borkat; Fadjarenie, Rien Agustin (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Infrastructure development is a strategic national priority in Indonesia, supported by State Capital Participation (PMN) in state-owned enterprises (SOEs), particularly in the construction sector. However, implementing PSAK 72 presents major challenges when applied to construction claims. This qualitative case study investigates how revenue from construction claims is recognized and disclosed in a SOE engaged in national infrastructure projects. Based on semi-structured interviews with board members and accounting standard-setters, the findings reveal a significant gap between PSAK 72’s normative requirements and field practices. While PSAK 72 requires sufficient evidence of performance obligations and high collectibility before recognizing revenue, in practice, revenue is recorded based on site instructions, technical progress, and managerial judgment—often without formal contract modifications. This divergence is driven by the pressure to meet performance targets and ensure financial continuity amid project funding constraints. The study contributes to the accounting literature by uncovering loopholes in claim recognition and proposing a context-sensitive governance framework. These findings offer valuable implications for regulators, auditors, and corporate governance institutions seeking to enhance transparency and alignment in public infrastructure financial reporting.